Diseño de una máquina lavadora automática de pistolas de pintura (2016)
This project consists in the design of an automatic washing machine guns paint for the automotive industry; this machine performs the washed a two gravity type spray guns, simultaneously in a time of 40 seconds. It also has two solvent containers with capacity of about 70 liters for each one, recirculating cyclically. This recirculation system has a filtering cartridge 75 µm. based on a filtering mechanism chemical solvents. It is automated through a mini PLC is mainly aimed at 4 valves with pneumatic actuators which are responsible for managing and storing the solvent into containers or into the wash chamber that is where the cleaning process is performed. It has a pumping system responsible for directing to the solvent container to the outlet nozzles.